THE ’STATE TRADITION’ IN AUSTRALIA: REASSESSING AN EARLIER VIEW - Wettenhall, Roger (The journal of contemporary issues in business and government, 2006)
This article seeks to revive interest in an Australian ’state tradition’ that has been undergoing continuous development since the first European settlements in the late 1700s and early 1800s. Recent attempts to redefine such a tradition miss many of the foundational elements. There has been a tendency to locate the beginnings in the federal ’settlement’ of 1901, and to see as outdated and irrelevant anything that happened before the current mood of marketising and privatising came to dominate our notions of political and economic correctness. Major changes have of course occurred in the nature of Australian statehood over the years, and they will continue to occur. However an understanding of the tradition restated in this article remains important for several reasons: because that tradition has furnished the foundations of so many of our national institutions; because it provides a standard against which the recent changes can be assessed; and because it will continue to influence and inform challenges to today’s economic-rationalist/NPM (New Public Management) paradigm. Such challenges will seek to take us further forward, not backward, but in a style that is inclusive rather than divisive.